Iron supplementation inhibits hypoxia-induced mitochondrial damage and protects zebrafish liver cells from death - Hu, Ruiqin; Li, Genfang; Xu, Qianghua; Chen, Liangbiao (Frontiers in Physiology, 2022)
Acute hypoxia in water has always been a thorny problem in aquaculture. Oxygen and iron play important roles and are interdependent in fish. Iron is essential for oxygen transport and its concentration tightly controlled to maintain the cellular redox homeostasis. However, it is still unclear the role and mechanism of iron in hypoxic stress of fish. In this study, we investigated the role of iron in hypoxic responses of two zebrafish-derived cell lines. We found hypoxia exposed zebrafish liver cells (ZFL) demonstrated reduced expression of Ferritin and the gene fth31 for mitochondrial iron storage, corresponding to reduction of both intracellular and mitochondrial free iron and significant decrease of ROS levels in multiple cellular components, including mitochondrial ROS and lipid peroxidation level. In parallel, the mitochondrial integrity was severely damaged. Addition of exogenous iron restored the iron and ROS levels in cellular and mitochondria, reduced mitochondrial damage through enhancing mitophagy leading to higher cell viability, while treated the cells with iron chelator (DFO) or ferroptosis inhibitor (Fer-1) showed no improvements of the cellular conditions. In contrast, in hypoxia insensitive zebrafish embryonic fibroblasts cells (ZF4), the expression of genes related to iron metabolism showed opposite trends of change and higher mitochondrial ROS level compared with the ZFL cells. These results suggest that iron homeostasis is important for zebrafish cells to maintain mitochondrial integrity in hypoxic stress, which is cell type dependent. Our study enriched the hypoxia regulation mechanism of fish, which helped to reduce the hypoxia loss in fish farming.